2000
DOI: 10.1111/j.1528-1157.2000.tb02217.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in the Elderly

Abstract: Summary:Purpose: The aim of this study was to evaluate the clinical charactcristics of elderly patients wilh epilepsy.Methods; Wc retrospectively reviewed the clinical records of I90 patients ( 104 males and 86 females) aged 60 years or older at the time of study.Resu1t.r: Epilepsies were classified as generalized in 33 patients (17.4%), partial in 145 (76.3%), and undetcrmincd in 12 (6.3%). Twenty-nine of 33 patients with gencraliLed epilcpsy were idiopathic, whereas all patients with partial cpilepsy were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 7 publications
4
41
2
4
Order By: Relevance
“…Our finding on male preponderance of seizures and epilepsies in elderly was also previously described by Hiyoshi et al 13 Prolonged postictal confusion was the most common postictal phenomenon found in this study, which was similar to previous study done by Stefan et al 14 Partial seizures are the most common type of seizure seen among the elderly patients with seizures. In a study by Hiyoshi et al, 76.3% elderly patients with seizures have partial seizures and similar findings were also reported by Sundaram.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding on male preponderance of seizures and epilepsies in elderly was also previously described by Hiyoshi et al 13 Prolonged postictal confusion was the most common postictal phenomenon found in this study, which was similar to previous study done by Stefan et al 14 Partial seizures are the most common type of seizure seen among the elderly patients with seizures. In a study by Hiyoshi et al, 76.3% elderly patients with seizures have partial seizures and similar findings were also reported by Sundaram.…”
Section: Discussionsupporting
confidence: 92%
“…27 Approximately, 60-70% of elderly epileptics can be adequately controlled with mono-therapy; 50-60% of those failing mono-therapy can be satisfactorily treated with an alternate second drug. 13 Studies have shown approximately 15-25% elderly epileptics experienced adverse reactions to antiepileptics, especially older AEDs . 28,30 In our study, 91 (59.1%) patients were on monotherapy and remaining 63 (40.9%) patients received two or more antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to treatment of elderly patients, anticonvulsant dosage and number of AEDs often lower in elderly-onset epilepsies as compared to younger-onset epilepsies as previously described by Besocke et al 14 and Arain et al 15 In the present study, patients who were having epilepsy from younger age required multiple antiepileptic drugs with increase in dosage than elderly onset group. Similarly Hiyoshi et al, 16 reported that mean number of antiepileptics used in the early onset group (<20 yrs) was 2.3, intermediate onset (20-49yrs) was 1.5 and 1.1 in late onset group, which clearly demonstrated that early onset group required more polytherapy. 16 Though incidence of adverse effects of AEDs are more common in elderly patients, in this study higher percentage of adverse effects in early onset group was due to prolonged use and higher dosage of antiepileptic drugs in this group.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly Hiyoshi et al, 16 reported that mean number of antiepileptics used in the early onset group (<20 yrs) was 2.3, intermediate onset (20-49yrs) was 1.5 and 1.1 in late onset group, which clearly demonstrated that early onset group required more polytherapy. 16 Though incidence of adverse effects of AEDs are more common in elderly patients, in this study higher percentage of adverse effects in early onset group was due to prolonged use and higher dosage of antiepileptic drugs in this group.…”
Section: Discussionmentioning
confidence: 76%
“…In any case, we may encounter patients with idiopathic epilepsies which started at much earlier ages and who have reached old age. Therefore, the possibility of a generalized epilepsy commencing in old age is remote, and given an patient aged over 60 who has developed epilepsy we should consider a focal epilepsy even when there is no clear focal start to the crises (Hiyoshi and Yagi 2000).…”
Section: Characteristics Of Epilepsy In the Elderlymentioning
confidence: 99%